Studi Identifikasi Stomata pada Kelompok Tanaman C3, C4 dan CAM - Achmad Yozar Perkasa; Totong Siswanto; Feni Shintarika; Titistyas Gusti Aji (Universitas Gunadarma, 2017)
Stomata is a biological components that largely determines the initial synthesis of organic compounds on physiological processes through the plant life cycle. The aim of this research was to study the different of stomata among plants C3, C4 and Crassulacean Acid Metabolism (CAM). This research was conducted at Microtechnique Laboratory of Agronomy and Horticulture Department, Agriculture Faculty, Bogor Agricultural University (IPB). The stomata preparations method by replica or mold method. The parameters that observed are number of stomata (for percentage of open and closed stomata) on the abaxial and adaxial layers of the leaves at magnification (40x10) diameter and stomatal density. The results showed that shading soybean plants had stomata density and number of opened stomata was high compared with soybean without shading C3 plants have high stomatal density and almost every plant species had opened stomata, whereas Crassulacean Acid Metabolism (CAM) plants have lower than others in densities in closed stomata conditions.